2022
DOI: 10.1101/2022.03.04.482962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strategic stabilization of arousal boosts sustained attention

Abstract: To meet their survival needs, organisms must continuously select which sensory stimuli to attend to and decide how much attention to pay. Attention’s selective aspect has been a cornerstone of behavioral and physiological study, whereas attentional intensity is poorly understood. Autonomic arousal is thought to strongly influence attentional intensity, but evidence is lacking, including regarding if and how organisms self-regulate their arousal to match attentional intensity to its utility. Here, we developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…Next, we performed three additional analyses to test whether the quadratic arousal-performance relationship was driven by significant behavioral or pupil events on the previous trial. Specifically, 1) we excluded all trials that followed erroneous responses (23.1% of all trials), possibly upregulating arousal, 2) we performed the analyses after regressing out task-evoked pupil responses on the previous trial (de Gee et al, 2014Gee et al, , 2022Waschke et al, 2021), and 3) we tested whether the quadratic arousal-performance relationship would also be revealed if the task-evoked pupil response in the previous trial was used as the measure of the pupil-linked arousal state. These analyses further solidified our main conclusions and indicated that the inverted Ushaped relationship between pre-stimulus (baseline) pupil size was not driven by response errors or task-evoked pupil responses on the previous trial (Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we performed three additional analyses to test whether the quadratic arousal-performance relationship was driven by significant behavioral or pupil events on the previous trial. Specifically, 1) we excluded all trials that followed erroneous responses (23.1% of all trials), possibly upregulating arousal, 2) we performed the analyses after regressing out task-evoked pupil responses on the previous trial (de Gee et al, 2014Gee et al, , 2022Waschke et al, 2021), and 3) we tested whether the quadratic arousal-performance relationship would also be revealed if the task-evoked pupil response in the previous trial was used as the measure of the pupil-linked arousal state. These analyses further solidified our main conclusions and indicated that the inverted Ushaped relationship between pre-stimulus (baseline) pupil size was not driven by response errors or task-evoked pupil responses on the previous trial (Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, although the observed quadratic arousalsensitivity relationship was clearly robust to task parameters, some previous studies in humans have also reported linear effects. In mice, primarily U-shaped functions are observed (de Gee et al, 2022;McGinley, David, et al, 2015;McGinley, Vinck, et al, 2015): mice perform best at an auditory detection task during quiet wakefulness, and worse during states of low and high arousal (including locomotion) (McGinley, David, et al, 2015). In humans however, the shape of the arousal-performance relationship appears to be less clear.…”
Section: Discussionmentioning
confidence: 99%
“…While the increase in response speed and history congruence over time (S1 Text) may argue against insufficient training as an alternative explanation for internal mode processing, it may also be indicative of waning arousal. The multiple mechanistic mappings to RTs and confidence warrant more direct measures of PLOS BIOLOGY arousal (such as pupil size [28,[63][64][65]67,68], motor behavior [63,68], or neural data [69]) to better delineate bimodal inference from fluctuations in global modulators of task performance.…”
Section: Task Engagement and Residual Motor Activation As Alternative...mentioning
confidence: 99%
“…Tone cloud stimuli consisted of repeating chords divided into 20 ms bins [de Gee et al, 2022]. Each chord was comprised of 5 semitones randomly selected between 1.5 kHz and 96 kHz.…”
Section: Auditory Stimulimentioning
confidence: 99%